Case report: Atypical anaphylactic reaction to Patent Blue V dye during breast cancer surgery - Misir Šitum, Stanka; Korečić Zrinjščak, Iva; Pečvarac, Maja; Šoštar, Andrea; Žaja, Ana; Tot, Tea (Frontiers in Oncology, 2022)
The most common causes of perioperative hypersensitive reactions are neuromuscular blocking drugs, latex and antibiotics, although there are other more emerging causative agents. Allergic reactions to Patent blue V (PBV) dye have been reported. Most of them are mild and presented with blue colouration of cutaneous plaque. The PBV dye is widely used in the identification of sentinel lymph nodes in patients with breast cancer and other malignancies. Here, we present a case of 33-year-old patient with carcinoma of the breast proposed for sentinel lymph node and skin sparing mastectomy with severe, life-threatening anaphylaxis which occured immediately after PBV dye was injected, with cardiopulmonal resuscitation and prolonged refractory hypotension. The patient was without previous exposure to PBV and signs of skin rash, erythema or bronchospasm, making the diagnosis and management of such cases challenging. A skin tests were performed on all drugs used in premedication and induction of anesthesia and PBV showed positive at IDT of 1:10. Physicians must always think of possible adverse reaction to PBV and for the potential risk of anaphylactic reaction immediately after the dye is injected, during anesthesia and other procedures.